The Relationship between Perception of HIV/AIDS and Attitude of Voluntary Counseling and Testing (VCT) among Housewives - Nina Sri; Eka Bati Widyaningsih; Indah Sri Wahyuni (Healthy-Mu Journal, 2024)
Housewives are one of the risk groups for contracting HIV/AIDS, especially women who have low knowledge and access to information and health services. This study aims to determine the relationship between perceptions about HIV/AIDS and VCT attitudes among housewives. This research is a quantitative study with a cross-sectional design conducted. The total population was 75 people. With a sampling technique using incidental sampling, a sample of 72 people was obtained. Data collection was carried out using an online questionnaire consisting of 30 closed questions covering perceptions of disease susceptibility, perceptions of disease seriousness, perceptions of obstacles, perceptions of self-confidence and VCT attitudes. The results of the analysis using the Chi-Square test obtained a P-value = 0.004 with an OR = 4.950 at a 95% CI. So, it is concluded that there is a relationship between perceptions of HIV/AIDS and VCT attitudes. Housewives who have a good perception about HIV/AIDS are 4,950 times more likely to have a positive attitude towards VCT. Perception cannot be separated from knowledge, so it is necessary to increase knowledge about HIV/AIDS and the benefits of VCT so that they have a positive attitude about VCT and do not become an obstacle to utilizing VCT services to find out the health condition of housewives.